Immunization with Parasite-Derived Apical Membrane Antigen 1 or Passive Immunization with a Specific Monoclonal Antibody Protects BALB/c Mice against Lethal Plasmodium yoelii yoelii YM Blood-Stage Infection - Narum, David L. (American Society for Microbiology, 2000)
We have purified apical merozoite antigen 1 (AMA-1) from extracts of red blood cells infected with the rodent malaria parasite Plasmodium yoelii yoelii YM. When used to immunize mice, the protein induced a strong protective response against a challenge with the parasite. Monoclonal antibodies specific for P. yoelii yoelii AMA-1 were prepared, and one was very effective against the parasite on passive immunization. A second protein that appears to be located in the apical rhoptry organelles and associated with AMA-1 was identified.